Saudi Arabia: seasons greetings from your friendly auto dealer - Parker, Mushtak (The Middle East, 1989)
This report on the annual Moslem pilgrimage to the holy cities of Makkah and Madinah features the increasing economic profiteering on the part of local, regional and foreign companies. As is amply shown, the hajj like Ramadan, is attracting consumerism with companies offering socalled specials as they do during Christmas in the West. Thus the Arabian Automotive Company, which is the agent of Britain's Range Rover in the kingdom, is offering free one-year full service for all vehicles bought during Ramadan and the hajj season. There is also increasing competition for the travellers cheque market. Other details concern the trade in livestock or the rents for accomodation often at exorbitant rates set by rogue landlords. (DÜI-Asd)